Physiological, morphological and anatomical leaf traits variation across leaf development in ’Corylus avellana’ - Catoni, Rosangela; Bracco, Francesco; Gratani, Loretta; Granata, Mirko Umberto (Mediterranean Botany, 2019)
The study analyzed the variations of physiological, morphological and anatomical leaf traits during its development in Corylus avellana L. saplings. Three different phases were identify during leaf development: the first phase (hereafter IP) considered in the developing leaves, the second phase (IIP) in the mature green leaves and the third phase (IIIP) in the senescent leaves. In particular, variations in parameters estimated from the photosynthetic light response curves, in chlorophyll fluorescence variables and in morphological leaf traits were analyzed during the three phases. The principal component analysis (PCA) carried out using all the considered morphological characters (leaf mass per area - LMA, and leaf tissue density - LTD) and physiological traits (the maximum net photosynthetic rates - ANmax, dark respiration rates - RD, light compensation point - LCP, light saturation point – LSP, maximum quantum yield - ɸmax, fluorescence-based maximum quantum yield of PSII photochemistry - Fv/FM and effective quantum yield of PSII photochemistry - ɸPSII) showed a complete separation among the considered phases. The results showed that the major differences occur between the phases IP and IIP. In particular, a greater variation was found for LMA, ANmax, RD. On the contrary a lower variation was observed for ɸmax which remain quite constant from IP to IIP indicating that chloroplasts present in juvenile leaves are fully functional.